Computational Study on the Pd-Catalyzed Pathway for the Formation of (R)-Methyl-(2-Hydroxy-1-Phenylethyl)Carbamate - Silvia González; Consuelo Mendoza Herrera; Lydia María Pérez Díaz; Laura Orea Flores; José Antonio Rivera Márquez; Ximena Jaramillo-Fierro (Molecules)
The formation of (R)-methyl-(2-hydroxy-1-phenylethyl)carbamate through Pd(PPh3)4-catalyzed synthesis was investigated using computational methods to elucidate the reaction pathway and energetic feasibility. Density functional theory (DFT) calculations confirmed that the direct reaction between (R)-(-)-2-phenylglycinol and methyl chloroformate is not spontaneous, requiring a catalyst to proceed efficiently. The study proposes a detailed mechanistic pathway involving ligand dissociation, intermediate formation, and hydrogenation. The role of Pd(PPh3)4 was examined, demonstrating its ability to stabilize reaction intermediates and facilitate key transformations, such as dehydrogenation and chlorine elimination. Two reaction pathways were identified, with Pathway 1 exhibiting a net energy of –84.7 kcal/mol and Pathway 2 showing an initial positive energy of 90.1 kcal/mol. However, the regeneration of key intermediates in Pathway 2 ultimately reduces the total reaction energy to –238.7 kcal/mol, confirming the feasibility of both routes. Computational results align with experimental NMR data, supporting the formation of the proposed intermediates. These findings provide valuable insights into catalyst optimization, suggesting that ligand modifications or alternative palladium-based catalysts could enhance efficiency. This study advances the understanding of Pd-catalyzed carbamate synthesis and offers a basis for future experimental and computational investigations.